JACOBUS DE BREDA Y LA IMPRENTA HOLANDESA EN LA TRADICIÓN DE OPERA ET DIES DE NICOLÁS VALLA - Moreno Hernández, Antonio; López Zamora, Jesús (Exemplaria Classica, 2016)
The aim of this article is to analyze the incunable editions of Nicolaus Valla’s Opera et Dies, printed in Deventer by Jacobus de Breda; to examine its liation relationships with other Ducht incunable editions and manuscript witness of the hesiodic translation by the Roman humanist; and, thereby, to establish its position in the stemma codicum of the text.